Características de contexto e sua inferência nos resultados do IDEB na rede municipal de educação de Foz do Iguaçu: uma análise comparativa entre as escolas com maior rendimento e escolas com menor rendimento - Gonzaga, Jean Carlos (2023)
The present study, titled "Contextual Characteristics and Their Inference on IDEB Results in the Municipal Education Network of Foz do Iguaçu: A Comparative Analysis between High-Performing and Low-Performing Schools," was conducted in the city of Foz do Iguaçu, in the state of Paraná, which, in 2019, gained national and state recognition for achieving a high score on the IDEB exam (7.1). This research delves into the realms of bibliographic and documentary analysis (examining the Pedagogical Political Project) and comparative studies, seeking to understand what education means in a capitalist society, as well as concepts such as quality, meritocracy, performativity, managerialism, large-scale assessment, and Comparative Education. To this end, comparative studies were conducted on the six schools with the highest IDEB scores in contrast to the six schools with the lowest IDEB scores, revealing the diverse social, cultural, and economic contexts in which they operate. From this study, it becomes clear that one of the major factors that differentiate them and influence higher or lower IDEB scores is the socio-economic context.